2020
DOI: 10.1021/acs.jmedchem.0c01001
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Reverse-Engineering of Estrogen Receptor Ligands as Potent Pan-Filovirus Inhibitors

Abstract: Filoviridae, including Ebola (EBOV) and Marburg (MARV) viruses, are emerging pathogens that pose a serious threat to public health. No agents have been approved to treat filovirus infections, representing a major unmet medical need. The selective estrogen receptor modulator (SERM) toremifene was previously identified from a screen of FDA-approved drugs as a potent EBOV viral entry inhibitor, via binding to EBOV glycoprotein (GP). A focused screen of ER ligands identified ridaifen-B as a potent dual inhibitor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…In addition to the eight compounds tested here, we showed in 20 Toremifene, sertraline, paroxetine, benztropine, bepridil, and imipramine have all been cocrystalized with the EBOV-GP and shown to bind directly to the EBOV fusion-loop-associated cavity. 11,21 In Schafer et al, we confirmed that these compounds, in addition to dibucaine and orphenadrine, interact with the EBOV fusion-loop-associated cavity via mutational analysis of key residues in that binding pocket.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to the eight compounds tested here, we showed in 20 Toremifene, sertraline, paroxetine, benztropine, bepridil, and imipramine have all been cocrystalized with the EBOV-GP and shown to bind directly to the EBOV fusion-loop-associated cavity. 11,21 In Schafer et al, we confirmed that these compounds, in addition to dibucaine and orphenadrine, interact with the EBOV fusion-loop-associated cavity via mutational analysis of key residues in that binding pocket.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, if approved, several investigational drugs may warrant testing in combinations. These include novel selective estrogen receptor modulators [73] and amodiaquine analogues [74], agents that target the HR2 region of EBOV GP2 [75,76], potentially broad-spectrum drugs that target the viral polymerase [77], or drugs that target other EBOV or host cell proteins or their interactions [78][79][80]. Moreover, the possibility exists of adding a third drug as supported by current therapeutic strategies against HIV [19,20] and HCV [21].…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms were also dependent on the interaction of hormones with their receptors. The inhibitory effect of estrogens on replication was documented [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. in a panel of viruses (for particulars see Table 1 ).…”
Section: Effect Of Oestrogen Receptor Modulators (Erms) On Viral Replicationmentioning
confidence: 99%
“…Unfortunately, the precise molecular mechanisms of action were deciphered only in a few cases and are usually independent of the interaction with the receptor. Clomifene, raloxifene, ridaifene (+XL-147) and toremifene act via attenuation of the interaction of SARS−CoV−2 or EBOLA with their target cells [ 37 , 40 , 41 , 42 , 43 , 44 ], where some role of the inhibition of SARS−CoV−2 spike protein interaction with receptor ACE2 may be expected [ 36 , 37 , 39 , 44 , 45 , 67 ]. ERMs seem to inhibit the glycan–glycan interaction between the spike protein and ACE2 and so reduces the virus entry to permissive cells [ 43 , 68 ].…”
Section: Effect Of Oestrogen Receptor Modulators (Erms) On Viral Replicationmentioning
confidence: 99%